2017
DOI: 10.24896/jmbr.2017713
|View full text |Cite
|
Sign up to set email alerts
|

Computational Evaluation of Pharmacokinetics and Potential Protein Targets of Ginger (Zingiber officinale)

Abstract: Ginger

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Clustering analysis was performed using ChemMine tools (http://chemmine.ucr.edu/) developed by Backman et al (2011). ADME/Tox screenings ADMET (Absorption, Distribution, Metabolism, Excretion and Toxicity) screening helps in detecting drug likeliness of compounds (Sanni and Fatoki 2017). The SMILES format of the ligands was loaded into the SwissADME server (http://www.swissadme.ch) and ADME screening was performed at default parameters (Daina et al 2017).…”
Section: Computational Design and Clustering Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering analysis was performed using ChemMine tools (http://chemmine.ucr.edu/) developed by Backman et al (2011). ADME/Tox screenings ADMET (Absorption, Distribution, Metabolism, Excretion and Toxicity) screening helps in detecting drug likeliness of compounds (Sanni and Fatoki 2017). The SMILES format of the ligands was loaded into the SwissADME server (http://www.swissadme.ch) and ADME screening was performed at default parameters (Daina et al 2017).…”
Section: Computational Design and Clustering Analysismentioning
confidence: 99%
“…In the post-genomic era, benefiting from the dramatic increase in bio-macromolecule and small molecule information, computational tools has been applied to most aspects of the drug discovery and development process, from target identification and validation to lead discovery and optimization (Sanni and Fatoki 2017). In this study, we computationally evaluate the structure and functions of xeronine as a potential therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…The systems biology techniques can be beneficial for pharmacological sciences. And, the reports showed pharmacological and toxicological effects of compounds assessed for an ailment [8,9]. For instance, systems pharmacology research revealed the inhibitory effects of three compounds from the ginger family in stroke risks [10].…”
Section: Introductionmentioning
confidence: 99%